A facile synthesis of meta- and para-terphenylglyoxamide-based peptidomimetics. Issue 48 (26th November 2020) - Yu, Tsz Tin; Bhadbhade, Mohan; Kuppusamy, Rajesh; Black, David StC; Kumar, Naresh
Graphical abstract: Highlights: A simple and efficient procedure for the synthesis of meta- and para -substituted terphenyl compounds. A facile synthesis of novel 5-biphenyl substituted N- acylisatins. Versatile and robust synthesis of terphenylglyoxamides under mild conditions. Abstract: A series of meta - and para -terphenylglyoxamide peptidomimetics have been synthesised by the ring-opening of 5-(biphenylyl)- N -acylisatins with alcohols, amines and amino acid methyl esters. The starting 5-(biphenylyl)isatins were synthesised via the Suzuki-Miyaura coupling reaction in a convenient and efficient manner.